2009
DOI: 10.4014/jmb.0901.00004
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant Activity of 5-HMF Isolated from Marine Red Alga Laurencia undulata in Free-Radical-Mediated Oxidative Systems

Abstract: Marine red algae of genus Laurencia are becoming the most important resources to produce unique natural metabolites with wide bioactivities. However, reports related to Laurencia undulata, an edible species used as folk herb, are rarely found to date. In this research, 5-hydroxymethyl-2-furfural (5-HMF) was isolated and characterized by nuclear magnetic resonance (NMR) from Laurencia undulata as well as other marine algae. The following characteristics of 5-HMF were systematically evaluated: its antioxidant ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 23 publications
5
70
1
1
Order By: Relevance
“…It has been suggested that HMF could be useful for the treatment or prevention of type I allergic diseases. Another studies demonstrated that HMF could be developed as a novel marine natural antioxidant or potential precursor for practical applications in the food, cosmetic, and pharmaceutical fields [Li et al, 2009].…”
Section: +mentioning
confidence: 99%
“…It has been suggested that HMF could be useful for the treatment or prevention of type I allergic diseases. Another studies demonstrated that HMF could be developed as a novel marine natural antioxidant or potential precursor for practical applications in the food, cosmetic, and pharmaceutical fields [Li et al, 2009].…”
Section: +mentioning
confidence: 99%
“…Lamouroux (Ceramiales, Rhodomelaceae), have proven to be a prolifi c source of secondary metabolites and have been the subject of intensive research in the fi eld of marine natural products (Faulkner, 2000;Guaratini et al, 2005;Cardozo et al, 2006;Cardozo et al, 2007). Many of Laurencia's metabolites have been found to possess a variety of biological activities such as antibacterial (Vairappan, 2003;Kladi et al, 2008;Vairappan et al, 2008), cytotoxic (Kladi et al, 2006;Kladi et al, 2007;Cen-Pacheco et al, 2011;Lhullier et al, 2010), antioxidant (Li et al, 2009), antimalarial (Topcufold with ethyl acetate prior to analysis by GC-MS.…”
Section: Introductionmentioning
confidence: 99%
“…Its molecular formula is C 3 H 6 O 3 . It has been reported that 5-HMF has favorable biological effects such as anti-oxidant activity, inhibiting sickling of red blood cells and ameliorate hemorheology (Abdulmalik et al 2005;Okpala 2006;Lin et al 2008;Li et al 2009;Villela et al 2009). …”
Section: Introductionmentioning
confidence: 99%